Improved all-polymer solar cell performance of n-type naphthalene diimide-bithiophene P(NDI2OD-T2) copolymer by incorporation of perylene diimide as coacceptor - Sharma, Sandeep; Kolhe, Nagesh B.; Gupta, Vinay; Bharti, Vishal; Sharma, Abhishek; Datt, Ram; Chand, Suresh; Asha, S. K. (Macromolecules, 2016)
Naphthalene diimide-bithiophene P(NDI2OD-T2) is a well-known donor-acceptor polymer, previously explored as n-type material in all-polymer solar cells (all-PSCs) and organic field effect transistor (OFETs) applications. The optical, bulk, electrochemical, and semiconducting properties of P(NDI2OD-T2) polymer were tuned via random incorporation of perylene diimide (PDI) as coacceptor with naphthalene diimide (NDI). Three random copolymers containing 2,2'-bithiophene as donor unit and varying compositions of naphthalene diimide (NDI) and perylene diimide (xPDI, x = 15, 30, and 50 mol % of PDI) as two mixed acceptors were synthesized by Stille coupling copolymerization. Proton NMR spectra recorded in CD Cl-3 showed that the pi-pi stacking induced aggregation among the naphthalene units could be successfully disrupted by the random incorporation of bulky PDI units. The newly synthesized random copolymers were investigated as electron acceptors in BHJ all-PSCs, and their performance was compared with P(NDI2OD-T2) as reference polymer. An enhanced PCE of 5.03% was observed for BHJ all-PSCs (all-polymer solar cells) fabricated using NDI-Th-PDI30 as acceptor and PTB7-Th as donor, while the reference polymer blend with the same donor polymer exhibited PCE of 2.97% efficiency under similar conditions. SCLC bulk carrier mobility measured for blend devices showed improved charge mobility compared to reference polymer, with PTB7-Th:NDI-Th-PDI30 blend device exhibiting the high hole and electron mobility of 4.2 x 10(-4) and 1.5 x 10(-4) cm(2)/(V s), respectively. This work demonstrates the importance of molecular design via random copolymer strategy to control the bulk crystallinity, compatibility, blend morphology, and solar cell performance of n-type copolymers.

Differential rubisco content and photosynthetic efficiency of rol gene integrated Vinca minor transgenic plant: correlating factors associated with morpho-anatomical changes, gene expression and alkaloid productivity - Verma, Priyanka; Khan, Shamshad Ahmad; Masood, Nusrat; Manika, N.; Sharma, Abhishek; Verma, Neha; Luqman, Suaib; Mathur, Ajay K. (Journal of Plant Physiology, 2017)
Transgenic plants obtained from a hairy root line (PVG) of Vinca minor were characterized in relation to terpenoid indole alkaloids (TIAs) pathway gene expression and vincamine production. The hairy roots formed callus with green nodular protuberances when transferred onto agar-gelled MS medium containing 3.0 mg/l zeatin. These meristematic zones developed into shoot buds on medium with 1.0 mg/l 2, 4-dichlorophenoxyacetic acid and 40 mg/l ascorbic acid. These shoot buds subsequently formed rooted plants when shifted onto a hormone-free MS medium with 6% sucrose. Transgenic nature of the plants was confirmed by the presence of rol genes of the Ri plasmid in them. The transgenic plants (TP) had elongated internodes and a highly proliferating root system. During glass house cultivation TP consistently exhibited slower growth rate, low chlorophyll content (1.02 +/- 0.08 mg/gm fr. wt.), reduced carbon exchange rate (2.67 +/- 0.16 mu mol m(-2) s(-1)), less transpiration rate (2.30 +/- 0.20 mmol m(-2) s(-1)) and poor stomatal conductance (2.21 +/- 0.04 mmol m-2 s(-1)) when compared with non-transgenic population. The activity of rubisco enzyme in the leaves of TP was nearly two folds less in comparison to non-transgenic controls (1.80 milliunits ml(-1) mg protein-1 against 3.61 milliunits ml(-1) mg protein-1, respectively). Anatomically, the TP had a distinct tetarch arrangement of vascular bundles in their stem and roots against a typical ployarched pattern in the non-transgenic plants. Significantly, the transgenic plants accumulated 35% higher amount of total TIAs (3.10 +/- 0.21% dry wt.) along with a 0.03% dry wt. content of its vasodilatory and nootropic alkaloid vincamine in their leaves. Higher productivity of alkaloids in TP was corroborated with more than four (RQ = 4.60 +/- 0.30) and five (RQ = 5.20 +/- 0.70) times over-expression of TIAs pathway genes tryptophan decarboxylase (TDC) and strictosidine synthase (STR) that are responsible for pushing the metabolic flux towards TIAs synthesis in this medicinal herb.

Overexpression of tryptophan decarboxylase and strictosidine synthase enhanced terpenoid indole alkaloid pathway activity and antineoplastic vinblastine biosynthesis in Catharanthus roseus - Sharma, Abhishek; Verma, Priyanka; Mathur, Archana; Mathur, Ajay (Protoplasma, 2018)
Terpenoid indole alkaloid (TIA) biosynthetic pathway of Catharanthus roseus possesses the major attention in current metabolic engineering efforts being the sole source of highly expensive antineoplastic molecules vinblastine and vincristine. The entire TIA pathway is fairly known at biochemical and genetic levels except the pathway steps leading to biosynthesis of catharanthine and tabersonine. To increase the in-planta yield of these antineoplastic metabolites for the pharmaceutical and drug industry, extensive plant tissue culture-based studies were performed to provide alternative production systems. However, the strict spatiotemporal developmental regulation of TIA biosynthesis has restricted the utility of these cultures for large-scale production. Therefore, the present study was performed to enhance the metabolic flux of TIA pathway towards the biosynthesis of vinblastine by overexpressing two upstream TIA pathway genes, tryptophan decarboxylase (CrTDC) and strictosidine synthase (CrSTR), at whole plant levels in C. roseus. Whole plant transgenic of C. roseus was developed using Agrobacterium tumefaciens LBA1119 strain having CrTDC and CrSTR gene cassette. Developed transgenic lines demonstrated up to twofold enhanced total alkaloid production with maximum ninefold increase in vindoline and catharanthine, and fivefold increased vinblastine production. These lines recorded a maximum of 38-fold and 65-fold enhanced transcript levels of CrTDC and CrSTR genes, respectively.